Phytodiversity in Riparian Ecosystems: A Study of Sabarmati River of Gandhinagar Municipal Corporation Area, Gujarat - Purani, Kuldip; Parmar, Rahul; Machhi, Darshan; Das, Lopamudra; Sugoor, R. K. (Indian Forester, 2025)
The present work was carried out with a principal aim of documenting the floristic vegetation richness in the riparian zone of the Sabarmati river flowing through the Gandhinagar Municipal Corporation (GMC) areas. Riparian vegetation was sampled by transect-based quadrates surveys. Line intersect transects have been laid perpendicular to the river bank towards the landward side in a zig-zag pattern. The present study has documented a total of 133 plant species belonging to 108 genera and 42 families from sampling sites along the Sabarmati riparian area of GMC area. The research findings reveal that the Shannon-Wiener diversity (H') index was estimated as 3.899, while Simpson's index (c) was calculated as 0.966 for the study area. The riparian area of the Sabarmati River, which passes through the GMC area, exhibits a floral population characterized by a moderate to high species diversity. The data obtained from the present study will contribute to the formulation of long-term management strategy of riparian flora, serving as a fundamental resource for monitoring and conserving the phytodiversity of the riparian area.